Measuring the value of a statistical life: problems and prospects - Orley C. Ashenfelter (Institute for the Study of Labor (IZA), 2006)
Tradeoffs between monetary wealth and fatal safety risks are summarized in the value of a statistical life (VSL), a measure that is widely used for the evaluation of public policies in medicine, the environment, and transportation safety. This paper demonstrates the widespread use of this concept and summarizes the major issues, both theoretical and empirical, that must be confronted in order to provide a credible estimate of a VSL. The paper concludes with an application of these issues to a particular study of speed limits and highway safety.
Keywords: J17; H43; I18; R4; 330; value of a statistical life; speed limits; safety risks; evaluation